Chinese household consumption: how much is enough? - Qingwang Guo (China Finance and Economic Review, 2015)
Background: As per currently accepted methodology of national economic accounting, China's household consumption rate is considered relatively low. This paper discusses the evolvement of China's consumption over time. Methods: Employing two different measures of consumption, I compare the growth rate of China's household consumption with the growth rates of China's economy, of its disposable income and of other nations' consumption. Results: The results of the analysis demonstrate that China's household consumption is growing vigorously in terms of both real growth rates of per capita household consumption and in total retail sales of consumer goods. Conclusions: Despite its current low level to GDP, China's household consumption has experienced a significant growth in recent years.
Keywords: 330; Household consumption; Weak; Paradox